Safety of Infliximab for the Eye Under Human T-Cell Leukemia Virus Type 1 Infectious Conditions in vitro - Uchida, Minami; Kamoi, Koju; Ando, Naoko; Wei, Chenxi; Karube, Hisako; Ohno-Matsui, Kyoko (Frontiers in Microbiology, 2019)
Use of biologics has been widely advocated for inflammatory diseases recently. Anti-tumor necrosis factor (TNF)-α antibody therapy is reportedly effective against ocular inflammation. However, side effects of TNF-α inhibition have been reported, particularly in the form of exacerbation of infections such as tuberculosis. Paradoxical reactions such as exacerbated inflammation are also well known. Around 20 million humans are infected with human T-cell leukemia virus type 1 (HTLV-1) globally, and this virus can cause adult T-cell leukemia, HTLV-1-associated myelopathy and HTLV-1 uveitis. As for ophthalmic concerns, it has not been identified whether anti-TNF-α antibody stimulates HTLV-1 infected cells and ocular cells to induce HTLV-1 uveitis in HTLV-1 carriers. Here we investigated the effects of anti-TNF-α antibody on ocular status under HTLV-1 infectious conditions using ocular cells and HTLV-1-infected cells in vitro. We used the ARPE-19 human retinal pigment epithelial cell line as ocular cells considered to play an important role in the blood-ocular barrier, and the MT2 HTLV-1-infected cell line. Jurkat cells were used as controls. Infliximab (IFX) was used as an anti-TNF-α antibody to achieve TNF-α inhibition. We evaluated the production of inflammatory cytokines and intercellular adhesion molecule (ICAM)-1, proliferation of ARPE-19, expression of TNF-α receptor (TNF-R) and HTLV-1 proviral DNA, and the percentage of apoptotic ARPE-19. Inflammatory cytokines such as interleukin (IL)-6, IL-8, TNF and ICAM-1 were significantly elevated through contact between ARPE-19 and MT2. Treatment with IFX tented to inhibit TNF production, although the level of production was low, but changes in IL-6, IL-8 and ICAM-1 remained unaffected. Expression of TNFR was unaltered by IFX treatment. HTLV-1 proviral DNA was not significantly changed with treatment. No change in cell growth rate or apoptotic rate of ARPE-19 were seen with the addition of IFX. In conclusion, IFX did not exacerbate production of inflammatory cytokines, and did not affect expression of TNFR, proliferation of ARPE-19, HTLV-1 proviral load or apoptosis of ARPE-19. These results suggest that IFX does not exacerbate HTLV-1-related inflammation in the eye and represents an acceptable treatment option under HTLV-1 infectious conditions.